SELF-RATED HEALTH AND MEDICAL CONDITIONS IN REFUGEES AND IMMIGRANTS FROM THE SAME COUNTRY OF ORIGIN (Iraqi Journal of Medical Sciences, 2016)
Background:Research suggests that refugees are at an increased risk for poor health outcomes as compared to immigrants. However, prior studies have compared refugees and immigrants from different countries and have failed to isolate specific war-related factors.Objective:To compare health outcomes and their determinants in refugees and immigrants from the same country of origin.Methods: A cross-sectional study based on a convenient sample and on self-report participants were conducted at Southeast Michigan during the period September to December 2009. A validated survey was used to examine refugees (n = 75) and immigrants (n = 65) from Iraq. The survey covered socioeconomics, lifestyle, violence exposure, self-rated health, and number of medical conditions (high blood pressure, fatigue, and backache, shortness of breath, gastrointestinal disorders, skin problems, and musculoskeletal problems). Group differences and predictors of health outcomes were assessed.Results:Refugees reported significantly more violence exposure than immigrants (p < 0.001). There were no significant differences in self-rated health or medical disorders between groups; however, violence exposure was the main predictor of health outcomes in refugees, whereas age was the main predictor in immigrants. Other predictors also varied by migratory group.Conclusion:Even though migration status did not directly influence health outcomes, results suggest that factors associated with migration status, e.g., violence exposure and age, do impact health. Future studies need to more carefully define and control for country-specific variables.Key Words:Health, Trauma, Violence, Emigrating, Iraq
Keywords: Health; Trauma; Violence; Emigrating; Iraq